EVALUATION OF IMPLEMENTATION OF INCLUSIVE EDUCATION PROGRAM FOR EARLY CHILDREN - HIDAYATI, Nurul (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2023)
This study aims to determine the various components that can influence the effectiveness of the inclusive education program. The program evaluation method and model used in this study is program evaluation research with a qualitative approach, using the Discrepancy Evaluation Model developed by Malcolm Provus using 4 stages. The results of this study indicate that the evaluation of early childhood inclusive education implemented by TKIT Assunah Cirebon City using the Discrepancy Model Evaluation (DEM) method is very important for the early childhood inclusive education community that requires special attention, where the implementation of inclusive education is in accordance with standard regulations. The results of the SWOT analysis show that the coordinate points (X, Y) are obtained, namely (3.5;-3) so that the intersection points are obtained which are in quadrant II which shows that there are more strengths than threats, weaknesses and opportunities. Where the strength is the use of a more simplified inclusive education curriculum so that it is easy to adapt to children with special needs. In addition, the existence of workshops/training for human resources can overcome threats to teacher competence as well as difficulties for class assistant teachers to balance learning for inclusive early childhood education because they have never participated in inclusive education program training. So that there is a need for support from the Principal and the Committee to provide training related to early childhood inclusive education for children with special needs.